Cervical cancer: New perspectives for prevention and control - Lazcano Ponce, Eduardo (2015)
The most important advance for global of control cervical cancer is the emergence of prophylactic vaccines against human papillomavirus (HPV) 16 and 18. A new phase starts that changes cervical cancer prevention and control paradigms, whose impact in the reduction in incidence and mortality will be observed by many of us in the next 20 years. The main challenge will be to establish an organized social response according to our physical infrastructure and human resources, our finantial factibility to implement the new technologies in the people and very importantly to consider the need of education and health promotion according to local and regional needs; all this to guarantee one of the main health rights, equity of access to all our population.